5.50x-25=65

Simple and best practice solution for 5.50x-25=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.50x-25=65 equation:


Simplifying
5.50x + -25 = 65

Reorder the terms:
-25 + 5.50x = 65

Solving
-25 + 5.50x = 65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + 5.50x = 65 + 25

Combine like terms: -25 + 25 = 0
0 + 5.50x = 65 + 25
5.50x = 65 + 25

Combine like terms: 65 + 25 = 90
5.50x = 90

Divide each side by '5.50'.
x = 16.36363636

Simplifying
x = 16.36363636

See similar equations:

| 7X+8x-4x-5=50 | | 8/12=x/32 | | =2t^2-84t+1025 | | 145x-55=56 | | 2n/3s | | (2x-7)^5/(2x-7)^3 | | 5-3x1/2 | | 35=3r+8 | | 9x^2-18x+79=0 | | 2x+50+x+10=2x+10 | | y7z3/y6z | | 20/100=x/5 | | 25=1d+21 | | 14a-93=49-59a | | (2x-7)^5/2x-7)^3 | | 2(a-1)-3/4w=3 | | 12x-12=56 | | -z/3=3 | | (7+7x)-7x= | | 5.95+175x=29.95 | | 29=2j+3 | | 5(m-2)+35=-4 | | -z-3=3 | | 37=6w+7 | | 3(x-5)=5(x+2) | | 3(-5x+40)+8=0 | | (14)/(5x^(2/3))*(2x^3) | | 4(9x+3)+2(12-x)= | | x+38=2(x+10)+4 | | 72x-44=45 | | 16=u/2 | | 0.06+2(0.07x-1)=2 |

Equations solver categories